Becoming braver through stanza format: Exploring intersecting identities beyond autistic - Dawn Louise Thibert (Murmurations, 2022)
In this article, I reflect on my professional journey in multiple contexts, in particular when working with autism was new territory for me. I found it more ethical and easier to express complexity through stanza form. I convey the therapeutic journey of in particular two young people I have worked with, and I highlight other themes that I have come across, using generalised case examples.  I highlight issues of intersectionality, particularly around gender identity, sexuality, culture and racialised identities. Throughout I relay how I work in an ethical way, opening space to promote intersectional expressions in complexity. I reflect on how finding my stanza voice has helped me express complexities more effectively than in prose, using stanzas.